2021
DOI: 10.1590/1980-5373-mr-2020-0496
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pozzolanic Activity of Glass Powder in Three Maximum Grain Sizes

Abstract: The addition of pozzolans has a potentially important role in the cement industry since using waste from other industries has important environmental benefits, including reduced CO 2 emissions from cement production. This study evaluates the pozzolanic activity of the glass powder in three different particle sizes (150 µm, 75 µm, and 45 µm, upper limits) and compares the results with those of other added pozzolans and technical standards found in the literature. Pozzolanicity was determined by four methods: Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This ground glass type has emerged as a viable alternative to traditional additives in cement (supplementary cementation material (SCM)). Scholarly articles, including key studies by Borges et al [24] and Wang et al in [25], have confirmed that these glass additives interact well chemically and mechanically with cement, making them a feasible choice for creating strong and durable concrete. The efficacy of this approach is primarily attributed to transforming glass waste into glass powder (GP) [26][27][28].…”
Section: Bibliographical Overviewmentioning
confidence: 94%
“…This ground glass type has emerged as a viable alternative to traditional additives in cement (supplementary cementation material (SCM)). Scholarly articles, including key studies by Borges et al [24] and Wang et al in [25], have confirmed that these glass additives interact well chemically and mechanically with cement, making them a feasible choice for creating strong and durable concrete. The efficacy of this approach is primarily attributed to transforming glass waste into glass powder (GP) [26][27][28].…”
Section: Bibliographical Overviewmentioning
confidence: 94%
“…According to the research carried out by [24], the results of the performance index with Portland cement indicate pozzolanic activity for the glass fractions #200 and #325 in the criteria of the American standard. Although the strength gain was slower in concrete with glass powder, as mixtures containing glass powder have a satisfactory performance in relation to drying shrinkage and alkaline reactivity, and there were indications that glass powder reduces the penetrability of the chloride ion of concrete, as well as the risk of chloride-induced corrosion of steel reinforcement in concrete [25].…”
Section: Pozzolanic Reactionsmentioning
confidence: 99%
“…In order to verify the pozzolanicity of the different glass parameters used indirectly (through mechanical resistance), the standard establishes that the mortar containing 25% of cement replacement by the supposedly pozzolanic material must reach a minimum limit of 90% of the compressive strength of the reference mortar (100% cement), for the material to be considered pozzolanic. By the criterion of NBR 5752 (21), all particle sizes used were considered pozzolanic, it can be seen that both for treated and untreated particles, the smaller the particle size used, the better the mechanical result, as in recent works that investigated the influence of granulometry on the pozzolanic properties of glass (25)(26)(27)(28)(29)(30).…”
Section: Pozzolanic Activity Index (Pai) -Mortarsmentioning
confidence: 99%
“…Many authors have investigated and proposed physical methods to enhance the pozzolanic properties of glass by reducing the size of glass particles and consequently increasing their surface area. It is widely agreed that reducing particle size and increasing surface area of glass effectively alters the kinetics of the chemical reaction toward the pozzolanic reaction (5,(25)(26)(27)(28)(29)(30). However, some authors discuss chemical pretreatments/methods aiming to increase the pozzolanicity of SCMs (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%